Formation of cognitive components of environmental consciousness in the process of protecting a language project - Butkevich, Yuliya (Journal of the Belarusian State University. Ecology, 2025)
The article identifies and substantiates the mechanisms of forming environmental consciousness through a component analysis of this concept. Environmental education, as structured learning aimed at deepening people’s understanding of environmental issues, biodiversity, and the characteristics of ecological systems, serves as a practical tool for shaping ecological consciousness. Environmental education is implemented through educational programs that convey information about the impact of human activities on the environment, inform about strategies for sustainable management and conservation of environmental quality. Psychological and pedagogical education also plays an important role, aiming todevelop thinking that fosters a caring attitude toward the environment. Methods of environmental education that stimulate and expand ecological knowledge and values include interactive workshops, discussions, and other public events that encourage the general public to reflect on their relationship with nature. The article examines the process of forming cognitive components of ecological consciousness using the «Language Project Defense» methodology. This methodology motivates students to independently research, present, and defend their ideas on pressing environmental issues. This process not only enhances students’ linguistic skills but also promotes the development of critical thinking on environmental topics. Students independently choose topics related to climate change, planetary sustainability, and nature conservation; the research process and project defense procedure activate students’ cognitive and verbal activities, facilitating the transformation of ideas into internal beliefs and, consequently, into active efforts to seek solutions. The article concludes that incorporating professionally oriented projects, thematically linked to sustainable development and solving environmental problems, into foreign language teaching enhances the effectiveness of forming cognitive components of ecological consciousness. Integrating such projects into linguistic education allows students to effectively apply environmental knowledge to achieve practical goals using a foreign language. Thus, two objectives are addressed: the activation of environmental knowledge and the reinforcement of ecological concepts, on one hand, and the consolidation of linguistic and rhetorical skills, on the other. This combination not only improves language proficiency but also cultivates informed, responsible citizens capable of consciously promoting environmental sustainability in their communities at a professional level.
Keywords: environmental consciousness; environmental education; environmental literacy; cognitive components of consciousness; protection of a language project